2006
DOI: 10.5424/sjar/2006042-190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tillage and water pressure head on the hydraulic properties of a loamy soil surface

Abstract: The effect of different tillage practices on soil hydraulic properties was studied in a mature, drip irrigated apricot orchard with a 7% slope, in Murcia (SE Spain). The soil had a loamy texture. Three soil tillage treatments were applied between the rows of trees: 1) control treatment (non-tilled, although weeds were cut to ground level using a blade attached to a tractor following the common practice of the area), 2) perforation treatment, in which soil surface was mechanically perforated with an adapted plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The high standard error can be attributed to variation in soil properties under trees because of tillage as observed in other studies (Coutadeur et al. , 2002; Abrisqueta et al. , 2006).…”
Section: Discussionsupporting
confidence: 55%
“…The high standard error can be attributed to variation in soil properties under trees because of tillage as observed in other studies (Coutadeur et al. , 2002; Abrisqueta et al. , 2006).…”
Section: Discussionsupporting
confidence: 55%
“…The change in the soil water content after rainfall depends mainly on the soil infiltration capacity, as well as on the rainfall characteristics. Previous research indicated that both soil tillage treatments increased the hydraulic conductivity of the soil surface (Abrisqueta et al, 2004), which led to lower runoff compared with the control treatment (Table 1). The soil tillage treatments (perforated and mini-catchment) caused a reduction of about 80% in runoff and about 70% in soil loss, with respect to the control, throughout the experimental period (Me´ndez et al, 2002;Plana, 2003), similar to that found in soils amended with several rates of organic urban solid refuse in a semiarid soil (Albaladejo et al, 2000).…”
Section: Water and Root Distributionmentioning
confidence: 91%
“…Lower CI in the cane rows of fields cultivated for 22 yr could be due to formation of surface crusts due to repeated tillage, whose effects could overcast the beneficial effects of roots in enhancing infiltration rates (IR) (Braunack et al, 2006). Tillage practices are expected to hasten initial IR due to increased macro-pore spaces (Coutadeur et al, 2002;Abrisqueta et al, 2006;Unger, 2009), thereby increasing infiltration in cane rows. Better root growth of sugarcane plants in cane rows resulting from fertilizer additions may have increased the number and length of continuous pores within the soil leading to better water infiltration.…”
Section: Discussionmentioning
confidence: 99%